2000
DOI: 10.1089/oli.1.2000.10.153
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicology and Pharmacokinetic Assessment of a Ribozyme (ANGIOZYME™) Targeting Vascular Endothelial Growth Factor Receptor mRNA in the Cynomolgus Monkey

Abstract: The potential acute toxicity of a ribozyme (ANGIOZYME) targeting the flt-1 vascular endothelial growth factor (VEGF) receptor mRNA was evaluated in cynomolgus monkeys following i.v. infusion or s.c. injection. ANGIOZYME was administered as a 4-hour i.v. infusion at doses of 10, 30, or 100 mg/kg or a s.c. bolus at 100 mg/kg. End points included blood pressure, electrocardiogram (ECG), clinical chemistry, hematology, complement factors, coagulation parameters, and ribozyme plasma concentrations. ANGIOZYME was we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…[80][81][82] Extensive pre-clinical studies in mice and monkeys have demonstrated no significant toxicities of angiozyme. 83,84 Angiozyme has been well tolerated by humans in phase I clinical studies, and has been evaluated in phase II trials in advanced and/or metastatic cancer patients alone or in combination with traditional chemotherapy. [85][86][87] However, regardless of the phase II trial results, the company has announced that it does not intend to develop angiozyme independently.…”
Section: B Agents Acting On the Receptor Of The Angiogenic Factormentioning
confidence: 99%
“…[80][81][82] Extensive pre-clinical studies in mice and monkeys have demonstrated no significant toxicities of angiozyme. 83,84 Angiozyme has been well tolerated by humans in phase I clinical studies, and has been evaluated in phase II trials in advanced and/or metastatic cancer patients alone or in combination with traditional chemotherapy. [85][86][87] However, regardless of the phase II trial results, the company has announced that it does not intend to develop angiozyme independently.…”
Section: B Agents Acting On the Receptor Of The Angiogenic Factormentioning
confidence: 99%
“…The typical dose required for efficacy ranges from 30 to 100 mg/m 2 . Hence, the downregulation of Flt-1 does not appear to cause any specific toxicity in the systems tested (23). Among the minor effects noted in a 28-day monkey study, kidney and liver cells accumulated basophilic granules, probably as a result of drug accumulation in these tissues.…”
Section: Figurementioning
confidence: 78%
“…Plasma samples obtained from animals treated with a single subcutaneous bolus injection of 48 or 118 mg/kg of RPI.13919 were used to compare the plasma concentrations of RPI.13919 obtained using either the DEAE/HPLC or the DEAE/C2-Empore/dialysis/CGE protocols and a phenol/chloroform /isoamyl alcohol extraction procedure previously described (27), followed by IEX-HPLC. Table 5 summarizes the observed plasma concentrations of RPI.13919 obtained by the different methods.…”
Section: Dosed Sample Analysismentioning
confidence: 99%